Afield. (2nd February 2018) - Pearson, Mike
Abstract : Reflections on and approaches to interdisciplinary collaboration in archaeology, cultural geography and performance. With the outline of a potential methodology and proposals for practice that draw upon experiences of creative endeavours in the field and in which scholarly and artistic are combined; and with reference to a series of performative outcomes.